Denileukin Diftitox (Ontak) as Maintenance Therapy for Peripheral T-Cell Lymphomas: Three Cases with Sustained Remission - Alejandra C. Fuentes; Ellen Szwed; Cathy D. Spears; Sandeep Thaper; Long H. Dang; Nam H. Dang (Case Reports in Oncological Medicine)
Peripheral T-cell lymphomas (PTCL) are rare but markedly aggressive forms of non-Hodgkin’s lymphoma (NHL). They carry a poor prognosis, with current therapeutic approach being generally ineffective. The most employed first-line treatment is CHOP (cyclophosphamide, doxorubicin, vincristine, and prednisone), which still results in high rates of relapses. Denileukin diftitox is a fusion protein combining the cytotoxic portion of the diphtheria toxin and the receptor-binding domain of the interleukin-2 (IL-2) molecule, thereby targeting cells expressing the IL-2 receptor, including both T-cell and B-cell lymphomas. It has been approved for the treatment of cutaneous T-cell lymphomas, and it has documented activity in PTCL both as a single agent and as part of combination therapy. This report documents three cases of PTCL where denileukin diftitox has been used as long-term maintenance therapy after complete remission was achieved. While the overall survival rate of patients with advanced stage, refractory PTCL is generally poor (with median overall survival of 5.5 months), the three patients described in this report are all experiencing an ongoing complete remission for more than four years.